2016
DOI: 10.5222/ankem.2016.018
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Methicillin Resistant Staphylococcus aureus Strains, Clinical Features of Patients and Factors Affecting Mortality

Abstract: ÖZET

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Nearly 80% of MRSA infections accumulate in the skin and soft tissues and spread rapidly. It has been shown that it causes diseases such as bursitis, osteomyelitis, arthritis, sinusitis, and urinary tract infection due to MRSA infection [39].…”
Section: Mrsa Carriagementioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 80% of MRSA infections accumulate in the skin and soft tissues and spread rapidly. It has been shown that it causes diseases such as bursitis, osteomyelitis, arthritis, sinusitis, and urinary tract infection due to MRSA infection [39].…”
Section: Mrsa Carriagementioning
confidence: 99%
“…Yüksekkaya et al stated that 48% of the cases with MRSA in blood culture were isolated from intensive care units, 47% from internal clinics, and 5% from surgical clinics [40]. In the study conducted by Zencir et al on hospitalized patients, it was reported that 84.6% of the patients with MRSA growth in their blood culture were obtained from the intensive care units and 14.4% from the samples from other clinics [39].…”
Section: Mrsa Carriagementioning
confidence: 99%